A Simplified Kinetic Modeling of CO2 Absorption into Water and Monoethanolamine Solution in Hollow-Fiber Membrane Contactors - Mai Lien Tran; Chi Hieu Nguyen; Kuan-Yan Chu; Ruey-Shin Juang (Membranes, 2023)
The absorption of CO2 from CO2-N2 gas mixtures using water and monoethanolamine (MEA) solution in polypropylene (PP) hollow-fiber membrane contactors was experimentally and theoretically examined. Gas was flowed through the lumen of the module, whereas the absorbent liquid was passed counter-currently across the shell. Experiments were carried out under various gas- and liquid-phase velocities as well as MEA concentrations. The effect of pressure difference between the gas and liquid phases on the flux of CO2 absorption in the range of 15–85 kPa was also investigated. A simplified mass balance model that considers non-wetting mode as well as adopts the overall mass-transfer coefficient evaluated from absorption experiments was proposed to follow the present physical and chemical absorption processes. This simplified model allowed us to predict the effective length of the fiber for CO2 absorption, which is crucial in selecting and designing membrane contactors for this purpose. Finally, the significance of membrane wetting could be highlighted by this model while using high concentrations of MEA in the chemical absorption process.